Kesalehan ibu dan pembentukan kepribadian anak: Tafsir Tematik QS. Ali Imran Ayat 35–36 - Lubis, Sufrin Efendi; Pane, Riem Malini (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study investigates the role of maternal piety in shaping children’s personality development based on a thematic interpretation of Surah Ali Imran (verses 35–36). Using a qualitative approach and literature-based design, the study draws data from Qur’anic verses, classical and modern tafsir, and supporting scholarly literature. Data were analyzed through content analysis within a thematic Qur’anic exegesis framework. The findings indicate four central points: (1) children are divine trusts endowed with innate purity, for which mothers bear primary moral responsibility; (2) while both parents share educational roles, fathers tend to fulfill material needs, whereas mothers focus on emotional and psychological nurturing; (3) mothers act as the child’s first educators and moral anchors; and (4) environmental factors play a major role in personality formation, with the mother as the most consistent influence. The study concludes that maternal piety plays a crucial role in shaping the moral, emotional, and spiritual dimensions of a child within Islamic teachings.